Design of rotating electrical machines - Pyrhonen, Juha (Wiley, 2014)
"This book is an in-depth essential reference of rotating electrical machine design theory and application. In the first part of the book the general theory governing the design of an electrical machine is presented; addressing the necessary fundamentals of electromagnetic theory; exploring possible winding arrangements and resistances; describing the behaviour of the magnetic circuit and flux leakage. After this introduction of principles the main body of the book focuses on the design of a rotating electrical machine. The book defines basic characteristics such as machine type (e.g. synchronous, asynchronous, DC and doubly salient reluctance machines) and type of construction (e.g. external pole, internal pole, axial flux and radial flux machines). It then moves on to provide a detailed analysis of the design process and properties of rotating electrical machines including the insulation and heat removal options. The book illustrates the necessary analytical calculations for machine design through direct design examples i.e. a permanent magnet motor for normal speeds with rotor surface magnets, traditional squirrel cage induction motor, a low speed high torque fractional slot permanent magnet motor etc."--